2017
DOI: 10.1177/1538192717739351
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Campus Climate and Experiences of Racial Microaggressions for Latinos at Hispanic-Serving Institutions

Abstract: This article demonstrates how Latinos attending Hispanic-Serving Institutions (HSIs) of various compositional diversities continue to experience racial microaggressions on campus. Using qualitative data from 40 in-depth interviews with Latino undergraduates enrolled at HSIs of different compositional diversities, findings reveal that participants attending an emerging HSI (23% FTE Latino enrollment [FTE]) and an HSI with a 45% FTE Latino enrollment reported experiencing more racial microaggressions compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Yet participants in the study stated that faculty often failed to address the blatant microaggressions, which was just as harmful. Specific examples included assumptions about Latinxs not being born in the United States, about Latinx families belonging to drug cartels, and about Latinx students being admitted because of affirmative action rather than merit or intellect (Sanchez, 2019). These findings coincide with another study at an emerging hSI where some Latinx students encountered racialized microaggressions with faculty and staff as well as observed racial segregation in the classroom that reflected external racialized patterns (Cuellar & Johnson-Ahorlu, 2020).…”
supporting
confidence: 58%
“…Yet participants in the study stated that faculty often failed to address the blatant microaggressions, which was just as harmful. Specific examples included assumptions about Latinxs not being born in the United States, about Latinx families belonging to drug cartels, and about Latinx students being admitted because of affirmative action rather than merit or intellect (Sanchez, 2019). These findings coincide with another study at an emerging hSI where some Latinx students encountered racialized microaggressions with faculty and staff as well as observed racial segregation in the classroom that reflected external racialized patterns (Cuellar & Johnson-Ahorlu, 2020).…”
supporting
confidence: 58%
“…In one study, Garcia (2016) discussed the effects of a hostile campus racial climate on student affairs professionals at HSIs. Another study by Sanchez (2017) finds that Latinx students have a greater chance at experiencing racial microaggressions at HSIs that only enroll 25% of Latinxs as opposed to 80%. Finally, Vega (forthcoming) studied racial conflict at an MSI and makes three major conclusions: (1) there is a gap in perception between administrators and students about dimensions of racial conflict (2) this gap in perception leads to dissatisfaction with and distrust for administrative response to racial conflict (3) informal learning about the institution, role of community members, and racial diversity initiatives occur after a public racial incident occurs.…”
Section: Writesmentioning
confidence: 99%
“…For example, Latinx students at one Hispanic-serving community college reported experiences with discrimination and bias in some student services offices (Cuellar & Johnson-Ahorlu, 2016). Similarly, Sanchez (2017) found that Latinx students at HSIs and emerging HSIs (institutions that enroll between 15-24% Latinxs) in Texas and California experienced microaggressions in the form of racial stereotypes and physical and social segregation, both inside and outside the classroom. Sanchez (2017), however, reported that students attending HSIs with higher concentrations of Latinxs experienced fewer instances of microaggressions.…”
Section: Cross-racial Interactions and Racial Tensions At Hsismentioning
confidence: 99%